ASSESSMENT OF HEAVY METALS CONTENT IN VLORA BAY USING ATOMIC ABSORPTION SPECTROMETRY - Tahiri, Valbona; Prenga, Dode; Denaj, Astrit; Vullkaj, Ilir (MATTER: International Journal of Science and Technology, 2019)
The presence of heavy metals in the maritime waters has been constantly considered as an important issue in the environmental aspects. In this framework, herein we report some findings from measurements of concentration of so called heavy metals in the sea waters of the Vlora (Albania). We obtained that the concentrations of Cu. Fe, Cd, Mn, are in the range of their average values in other Adriatic places. Usually the concentration of those elements depends on the positions where measurement have been made, indicating that isolated sources of pollution are likely to present. We observe a slight decrease of the construction of Cu and Mn following maritime local flows. Next we obtain that the concentration of Cu. Cd. Fe, Mn, Ni in the near coast line stabilize below 1m of depth supporting the idea that the sediments or the floor of the sea coast are not source and major factors of pollution with those elements are atmospheric process, water discharges and seawater flows.